PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS TENAGA KERJA DAN PERINDUSTRIAN KOTA PADANG - Gito Septa Putra; Jhon Fernos (LP2M Universitas Bina Bangsa, 2023)
This study aims to analyze the effect of work discipline and work motivation on employee performance at the Department of Labor and Industry in the city of Padang. This research uses quantit ative methods. The population is all employees at the Department of Labor and Industry in the city of Padang with a total of 52 respondents and a sample of 52 respondents. The sampling technique is a saturated sampling technique where all the population is taken as a sample. Data analysis used multiple linear regression analysis using the SPSS application. The results showed that work discipline had a positive and significant effect on employee performance at the Padang city labor and industry office and work motivation had a positive and significant effect on employee performance at the Padang city labor and industry office